Development and Mixed-Methods Evaluation of a Pain Assessment Video Training Program for Long-Term Care Staff. (2013) - Gagnon, Michelle M; Hadjistavropoulos, Thomas; Williams, Jaime
Abstract : INTRODUCTION: Inadequacies in pain assessment and management in long-term care have been well documented. Insufficient pain education and inaccurate beliefs about the nature of pain and aging have been identified as possible contributors. The present study addresses the need for improved, efficient and feasible continuing pain education through the use of an assessment training video. METHODS: A total of 148 long-term care staff viewed and evaluated the training video. Knowledge changes and pain beliefs were assessed postvideo and at a four-week follow-up. Beliefs about pain, as well as pain and aging, were also examined using multivariate procedures to determine whether these variables influenced participants' evaluation of the video. Focus groups were also conducted, and transcripts were analyzed using thematic content analysis. RESULTS: Pain assessment knowledge improved postvideo and at the four-week follow-up. Participants positively evaluated the content and quality of the video. Individuals who held stronger beliefs (at baseline) about the organic nature of pain provided more positive evaluations. Barriers to implementation of practices in the video identified by the focus groups (and qualitative analysis) included time, workload and resistance to change. Facilitators to implementation included continued management support and observing the benefits to implementation. DISCUSSION: The present study provides support for the use of video training. However, based on the focus group results, top-down implementation approaches with ongoing management involvement throughout the implementation process may be needed to achieve sustained changes in pain assessment practices. A model useful for sustained implementation was proposed and discussed, and is hoped to facilitate future research.